Kajian Faktor-faktor Penentu Kecekapan Bank Perkreditan Rakyat (Bpr) Di Jawa Barat Indonesia - Ilyas, Yusri (2021)
Bank Perkreditan Rakyat (BPR) plays an important role in the Indonesian economy, as they contribute to the provision of capital for local industries, especially micro, small, and medium enterprises (UMKM). For that reason, the Indonesian government also facilitates the formation of new BPRs which contribute to the increase in the number of BPRs in Indonesia. Therefore, a study on the efficiency of BPRs in managing its resources is of high importance. Specifically, the objective of this study is to measure BPR’s efficiency and identify the independent variables that affect the efficiency of BPRs. In line with previous studies, the seven independent variables used in this study are Non-Performing Loans (NPL), age, size of BPR, total credits, total equity, ROA, and type of BPR (conventional or sharia). This study uses a non-parametric method known as the Data Envelopment Analysis (DEA) in order to analyze BPR’s efficiency. In addition, a Tobit regression is conducted to determine the relationship between the dependent and independent variables. This study uses a panel data of 254 BPRs throughout West Java for a period from 2012 to 2016. This study finds that the level of BPR’s efficiency is different across all the sample that is studied. The findings show that 249 BPR are not efficient, four BPR are moderately efficient, three BPR are efficient and only two BPR are very efficient in managing their resources. In addition to that, age of BPR, size of BPR, credit financing, total equity, and type of BPR are found to have an impact on BPR efficiency.